Transient hypertriglyceridemia: a common finding during Epstein-Barr virus-induced infectious mononucleosis - Emilio-Manuel Páez-Guillán; Joaquín Campos-Franco; Rosario Alende; Yago Garitaonaindía; Arturo González-Quintela (Lipids in Health and Disease, 2021)
Abstract Background Hypertriglyceridemia can occur in lymphoproliferative disorders. Infectious mononucleosis is a self-limiting, benign lymphoproliferative disorder. This study aimed to investigate the serum triglyceride concentrations and their change over time in patients with infectious mononucleosis. Methods We evaluated an adult patient with severe hypertriglyceridemia (>1000 mg/dL) during infectious mononucleosis and reviewed the records of 360 patients admitted to our hospital because of infectious mononucleosis (median age, 19 years; range, 15-87 years; 51.4% male). We compared the serum triglyceride concentrations with those of a control sample from the general population (n=75). A second triglyceride measurement, obtained during convalescence (median of 30 days after the initial determination), was available for 160 patients. Results The triglyceride concentrations in the acute phase (median: 156 mg/dL) were significantly higher than those of the controls (median, 76 mg/dL; P<0.001). A total of 194 (53.9%) patients presented with hypertriglyceridemia (>150 mg/dL), which was more common in the patients older than 30 years than in the younger patients (78.6% vs. 50.6%; P<0.001). A significant correlation (P<0.005) was observed between the triglyceride levels and white blood cell counts, total cholesterol levels, and liver damage markers. The triglyceride concentrations decreased during convalescence (P<0.001) and were lower than the initial measurement in 83.7% of the cases. Conversely, the total cholesterol concentrations during the acute phase were lower than those of the controls and increased during convalescence (P<0.001). Conclusions Patients with severe infectious mononucleosis frequently show mild, transient hypertriglyceridemia. Further studies are needed to elucidate the mechanisms underlying this finding.